2020
DOI: 10.1177/0020764020975792
|View full text |Cite
|
Sign up to set email alerts
|

The mediating role of knowledge on the contact and stigma of mental illness in Hong Kong

Abstract: Background: Although knowledge is a crucial component in contact theory delineating how prejudice changes toward out-groups with stigmatized conditions, little is known about the mediating role of knowledge on contact, stigmatizing attitudes, and behaviors toward mental illness. Aim: This study aimed to examine the mechanism underlie contact and stigma change by knowledge. Methods: A total of 366 participants including family members (FM), mental health providers (MHP), and community residents (CR) recruited a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
23
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 70 publications
6
23
2
Order By: Relevance
“…In contrast to previous research, our study did not identify significant effects of sociodemographic variables, such as age (Wu et al 2020 ), financial problems (Zhang and Ma 2020 ), or educational level (Dong et al 2020 ). However, the sample of our study is quite homogeneous: most of the women reported a high educational level and a low financial affectation.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to previous research, our study did not identify significant effects of sociodemographic variables, such as age (Wu et al 2020 ), financial problems (Zhang and Ma 2020 ), or educational level (Dong et al 2020 ). However, the sample of our study is quite homogeneous: most of the women reported a high educational level and a low financial affectation.…”
Section: Discussioncontrasting
confidence: 99%
“…Among the general public, research found knowledge to have a small-to-medium effect in reducing stigma (Morgan et al, 2018). Among FM and MHW, knowledge is especially crucial in facilitating better understanding and management of PMI’s conditions (Fang et al, 2020; Madianos et al, 2005; Shin, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Such moralizing views may contribute to more severe public stigma towards mental illness (Chien et al, 2014; Lee et al, 2005). Community residents (CR) have limited mental health knowledge, fear PMI’s propensity to violence and oppose psychiatric rehabilitation facilities near their residence (Chan et al, 2016; Fang et al, 2020; Siu et al, 2012). Moreover, stigmatizing views are commonly shared by FM and MHW in Hong Kong (Chien et al, 2014; Lee et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although our ndings are promising with regards to reducing stigmatizing attitudes, increasing willingness to engage in relationships with people with mental illness, and increasing provider empathy, these short-term results need to be interpreted with caution because of small sample size and the lack of a comparison condition. Nevertheless, the current study contributes to a limited body of research from low-and middle-income countries that examined interventions to reduce mental health-related stigma among healthcare providers (12).…”
Section: Discussionmentioning
confidence: 99%